Kontemplasi Citayem Fashion Week sebagai Ekspresi Generasi Milenial dan Pendidikan Masyarakat melalui Fashion - Nawawi, Kholil; Indriya, Indriya (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Talking about dress style is an expression of how to dress based on Religion, Communication, Education, Economics, and Politics. Clothing is the most easily recognizable artifact in a civilization. Citayam Fashion Week is a means of expression for the millennial generation from Citeyam, Bojonggede, and Depok, which makes the Dukuh Atas area of Jakarta which is a play on the SCBD Senayan Citayam Bojonggede Depok which is a place to gather or hang out with a typical millennial style as a place of expression through fashion. From that, the millennial generation also needs to understand the essence of education. Education is a process of changing something to the point of perfection (maturity), which is done gradually. On the other hand, society is a group of people who form a semi-closed (or semi-open) system, in which there are various kinds of interactions between individuals and individuals, individuals with groups, and groups with groups. This study aims to find the results of the viral contemplation of Citayam Fashion Week as an Expression of the Millennial Generation with the perspective of Islamic Education (Tarbiyah). Researchers in this study used a library research approach. The results of the study found findings, namely; first, family and society have a very big role in determining millennial identity; Second, creativity arises from the existence of a hedonistic culture (pleasing oneself) to express itself; Third, social media as a means of expression for millennials to shape behavior, as well as a reflection of society; Fourth, the challenges for educators in the era of globalization are getting higherKeywords: Citayam Fashion Week; Millennial Generation; Public Education; Fashion AbstrakBerbicara mengenai gaya berpakaian merupakan ekspresi cara berpakaian yang dilatar belakangi oleh Agama, Komunikasi, Pendidikan, Ekonomi, dan Politik. Pakaian adalah artefak yang paling mudah dikenali di suatu peradaban. Citayam Fashion Week merupakan sarana ekspresi generasi milenial dari Citeyam, Bojonggede dan Depok, yang menjadikan kawasan Dukuh Atas Jakarta yang diplesetkan menjadi SCBD Senayan Citayam Bojonggede Depok yang menjadi tempat berkumpul, atau nongkrong dengan gaya khas milenial sebagai ajang ekpresi melalui fashion. Dari hal itu, para generasi milenial perlu juga memahami esensi pendidikan. Pendidikan merupakan proses perubahan sesuatu sampai pada titik kesempurnaan (kedewasaan), yang dilakukan secara bertahap. Di sisi lain Masyarakat merupakan sekelompok orang yang membentuk sebuah sistem semi tertutup (atau semi terbuka), yang didalamnya terdapat berbagai macam interaksi antara individu dengan individu, individu dengan kelompok maupun kelompok dengan kelompok. Penelitian ini bertujuan untuk mencari hasil dari kontemplasi viralnya Citayam Fashion Week sebagai Ekspresi Generasi Milenial dengan perspektif Pendidikan Islam (Tarbiyah). Peneliti dalam penelitian ini menggunakan pendekatan studi kepustakaan (library research). Hasil penelitian menemukan temuan yaitu; pertama, keluarga dan masyarakat memiliki peran yang sangat besar di dalam menentukan identitas milenial; Kedua, kreatifitas muncul dari adanya budaya hedonisme (menyenangkan diri sendiri) mengekspresikan dirinya sendiri; Ketiga, sosial media sebagai sarana ekpresi milenial membentuk prilaku, sekaligus cerminan masyarakat; Keempat, tantangan bagi para pendidik di era globalisasi semakin tinggiKata Kunci: Citayam Fashion Week; Generasi Milenial; Pendidikan Masyarakat; Fashion